Preoperative taxane-based chemotherapy in a standardized protocol for locally advanced breast cancer - Chan, Arlene; Willsher, P.; Hastrich, D.; Anderson, J.; Barham, T.; Latham, B.; Redfern, A.; Van der Schaaf, A.; Thomson, J.; Joseph, D.; Ingram, D. (Wiley-Blackwell Publishing Ltd., 2012)
Aims: To assess the feasibility of a standardized multidisciplinary protocol for the management of locally advanced breast cancer (LABC). We also evaluated the accuracy of magnetic resonance imaging (MRI) and positron emission tomography (PET) in predicting the extent of residual disease. Methods: Patients with LABC were offered preoperative chemotherapy of docetaxel 75 mg/m2, doxorubicin 50 mg/m2, cyclophosphamide 500 mg/m2 (TAC), every 21 days for six cycles, until progression or intolerable toxicity. MRI and PET were performed at baseline and six cycles. Patients underwent a mastectomy or complete local excision, followed by radiotherapy. Trastuzumab and endocrine treatment were recommended where appropriate. Results: Between April 2005 and October 2006, 51 patients were included from three institutions, and 50 received TAC (90% commenced within 35 days of diagnosis), with 44 patients completing six cycles (88%). Pathological complete response was seen in 10 patients (19.6%); all had invasive ductal carcinoma. No patient with invasive lobular carcinoma achieved pathological complete response. MRI was the most accurate method of assessing the extent of residual cancer. In total, 45 (88%) patients underwent surgery within the protocol-specified time and 12 (23%) patients had breast conservation surgery. At a median follow-up of 41.3 months, there were three local recurrences. Ten patients (19.6%) developed distant metastases, resulting in an 80% actuarial disease-free survival. Conclusion: This regimen of TAC is effective and well-tolerated and is likely to result in improved outcomes since patients can receive optimal multimodality treatments.